2012
DOI: 10.1111/ecc.12030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oesophagectomy on physical fitness and health-related quality of life in patients with oesophageal cancer

Abstract: Although several studies have reported the impact of oesophagectomy on health-related quality of life (HRQOL), none has objectively assessed its impact on physical fitness. This study aimed to evaluate the impact of oesophagectomy on physical fitness and HRQOL in patients with oesophageal cancer. In this prospective study, we investigated 30 consecutive patients with newly diagnosed resectable oesophageal cancer who were scheduled to receive either neoadjuvant chemotherapy followed by surgery or surgery alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
6
31
0
Order By: Relevance
“…Even in the three patients who underwent video-assisted thoracic surgery, the mean decrease in 6MWD was 60 m, above the clinically important value. Our results were consistent with the previous report by Tatematsu et al that 6MWD and knee-extensor muscle strength, which were measured on the day of hospital discharge (median 21 days after surgery), were significantly decreased after esophagectomy [13]. Tatematsu et al also reported that the change in the physical functional score on EORTC QLQ-C30 was significantly affected by that in the 6MWD by multiple regression analysis [13].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Even in the three patients who underwent video-assisted thoracic surgery, the mean decrease in 6MWD was 60 m, above the clinically important value. Our results were consistent with the previous report by Tatematsu et al that 6MWD and knee-extensor muscle strength, which were measured on the day of hospital discharge (median 21 days after surgery), were significantly decreased after esophagectomy [13]. Tatematsu et al also reported that the change in the physical functional score on EORTC QLQ-C30 was significantly affected by that in the 6MWD by multiple regression analysis [13].…”
Section: Discussionsupporting
confidence: 92%
“…At our institution, perioperative pulmonary rehabilitation is routinely performed on patients who underwent esophagectomy. In addition, physical, mental, and QOL status are routinely assessed before and after surgery as the perioperative rehabilitation program according to previous reports and guidelines [2, 10, 13, 1619]. Patients are allowed to refuse the assessment if they do not wish.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some patients can be cured, the treatment for esophageal cancer is protracted, diminishes the quality-of-life, and is lethal in a significant number of cases. [1,2] Prognosis of esophageal cancer is generally poor because of its biological aggressiveness and anatomic characteristics. [3] Esophagectomy, the surgical removal of all or part of the esophagus, is a surgical procedure that is associated with high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%